2010
DOI: 10.1371/journal.pone.0010850
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Peptidoglycan Promoted Breast Cancer Cell Invasiveness and Adhesiveness by Targeting Toll-Like Receptor 2 in the Cancer Cells

Abstract: Chronic bacterial infection increased the risk of many solid malignancies and the underlying mechanism is usually ascribed to bacterial-caused inflammation. However, the direct interaction of infectious bacteria with cancer cells has been largely overlooked. We identified that highly metastatic breast cancer MDA-MB-231 cells expressed high level of Toll-like receptor 2 (TLR2) in contrast to poorly metastatic breast cancer cells and homogenous untransformed breast cells. TLR2 in MDA-MB-231 cells were actively t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 48 publications
2
34
1
Order By: Relevance
“…Moreover, the IgG-type antibodies against PGN endured for 8 weeks after the last immunization, which indicates that MAP-P31 as a thymus-dependent antigen induces a secondary antibody response to S. aureus, as only thymus-dependent antigens can induce secondary antibody responses and persist in the body for this length of time. We also found that MAP-P31 stimulated pMØ to release IL-6 and TNF-a independently of LPS, which suggests that MAP-P31 can also mimic the biological activities of PGN, as PGN plays a vital role in inflammation by inducing excessive amounts of inflammatory factors (Lin al., 2010;MacKenzie et al, 2010;Visser et al, 2005;Xie et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the IgG-type antibodies against PGN endured for 8 weeks after the last immunization, which indicates that MAP-P31 as a thymus-dependent antigen induces a secondary antibody response to S. aureus, as only thymus-dependent antigens can induce secondary antibody responses and persist in the body for this length of time. We also found that MAP-P31 stimulated pMØ to release IL-6 and TNF-a independently of LPS, which suggests that MAP-P31 can also mimic the biological activities of PGN, as PGN plays a vital role in inflammation by inducing excessive amounts of inflammatory factors (Lin al., 2010;MacKenzie et al, 2010;Visser et al, 2005;Xie et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that TLR9 overexpression and stimulation with hypomethylated DNA augment the migratory capacity of cancer cells [84]. In addition, highly metastatic human breast cancer cells express high levels of TLR2 in contrast to poorly metastatic breast cancer cells and homogenous untransformed breast cells [85]. TLR8 expression is also an independent prognostic factor for CRC [86].…”
Section: Expression Of Toll-like Receptors Is Associated With the Promentioning
confidence: 99%
“…Lm activates MAPKs and NF-jB in tumor cells through TLR2 signaling, resulting in the increased production of NO and IL-6 and increased proliferation of tumor cells [94]. Activation of TLR2 in breast cancer cells by peptidoglycan (PGN) from infectious bacterium Staphylococcus aureus (PGN-SA) induces TLR2-dependent NF-jB activation and secretion of IL-6 and TGF-b and promotes the invasiveness and adhesiveness of the cancer cells in vitro, illustrating a new link between component of infectious bacteria and the cancer [85]. PGN-SAstimulated NF-jB activity results in STAT3 and Smad3 sequential activation, which contributes to invasiveness and adhesiveness [85].…”
Section: Tlr7mentioning
confidence: 99%
See 1 more Smart Citation
“…This heterogeneity is evident from the contradictory findings from studies that investigated TLR2 signaling in various tumor models [3,11,53,56]. TLR2 ligation has been reported to induce either promising anti-cancer activity [39,[57][58][59][60] or confounding pro-tumorigenic effects [61][62][63][64][65]. Clearly, characterization of the precise function of each TLR in any given tumor type is critical [3], and the contrasting roles of TLR2 are thought to have significantly impaired the development of TLR2 agonists as adjuvants in anti-cancer immunotherapy [2,66].…”
mentioning
confidence: 99%